Acute heart failure : putting the puzzle of pathophysiology and evidence together in daily practice - Krüger, Wolfgang 1950- (Cham, Switzerland : Springer, 2017)
Acute heart failure is a potentially life threatening situation where correct, rapid therapy can save lives. Information from the latest research and studies has been used to update this text to bring the latest understanding of the pathophysiology together with a practical guide to diagnosis and management using an evidenced based approach. Since the first edition of Acute Heart Failure, this research has brought to light three important issues to be integrated into a second edition. First, the so-called "vascular heart failure" has been identified as a common and decisive mechanism provoking acute heart failure due to the coupling and interaction between the heart (right and left heart) and the large vessel systems (aorta and pulmonary artery). Second, the interaction and cross-talk between heart and kidneys, the so-called 'cardiorenal syndrome' has been identified as another feature of acute heart failure syndromes. Third, we have new knowledge and updated points of views about the development of pulmonary hypertension in patients suffering from heart failure, the group 2 of the classification system of pulmonary hypertension. These are all covered in this second edition. This revision to a seminal text is a valuable addition to any practitioner who treats patients with acute heart failure and wants a deeper understanding of the condition.
Keywords: INSUFICIENCIA CARDIACA; INSUFICIENCIA CARDIACA -- TRATAMIENTO; CORAZÓN -- ENFERMEDADES -- FISIOPATOLOGÍA; MEDICINA BASADA EN LA EVIDENCIA